2020
DOI: 10.1017/9781316810071
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Politeness

Abstract: It is increasingly important in our globalised world for people to successfully manage interpersonal relationships. This is the first book to tackle this vital topic, by taking an interdisciplinary approach to exploring the process of relating across cultures. Drawing together key concepts from politeness theory, intercultural communication, and cross-cultural/intercultural psychology, it provides a robust framework for analysing and understanding intercultural encounters. It explores the ways in which indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 306 publications
1
16
0
Order By: Relevance
“…This can be accomplished by discussing the components of various values, beliefs, and behavioral standards. Group identities, cultural traditions, and individual personality qualities may all have an impact on the dynamics of relationships, as depicted in the image below (Spencer-Oatey & Kádár, 2021).…”
Section: Intercultural Interactions: a Framework To Intercultural Com...mentioning
confidence: 99%
See 2 more Smart Citations
“…This can be accomplished by discussing the components of various values, beliefs, and behavioral standards. Group identities, cultural traditions, and individual personality qualities may all have an impact on the dynamics of relationships, as depicted in the image below (Spencer-Oatey & Kádár, 2021).…”
Section: Intercultural Interactions: a Framework To Intercultural Com...mentioning
confidence: 99%
“…Overview of the influence of culture on interaction (Spencer-Oatey & Kádár, 2021) Participants in this study should be mindful of the many levels of context depicted in the picture above when creating intercultural contacts. To achieve this goal, it is necessary to take into account the factors that contribute to the expression of distinct norms, values, and beliefs in social behavior.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This view contrasts the conception of language awareness as knowledge of simplistic pragmatic rules (e.g., using would you instead of can you to show politeness) (Liddicoat & McConachy, 2019). One reason for avoiding teaching politeness as a set of rules is that, as Spencer-Oatey and Kádár (2021) argue, politeness conventions in utterances or behaviour can significantly vary and mean differently depending on individual interpretations. As such, the emphasis of interculturally-oriented pragmatics instruction is on helping learners recognise different ways of understanding social concepts such as politeness, formality, and appropriateness.…”
Section: Iip Feature 2: Multilingual Views Of Language Learning and Usementioning
confidence: 99%
“…This way of prescribing linguistic forms as polite or not indicates a binary and restricted view of appropriateness(Liddicoat & McConachy, 2019). Moreover, language is rarely inherently polite in itself because its use and interpretation are influenced by individual, contextual, and cultural factors(Spencer-Oatey & Kádár, 2021). Previous studies also found that textbooks present inventories of decontextualized phrases ordered from formal/polite, to informal but do not define what these concepts mean (e.g.,McConachy, 2013a;…”
mentioning
confidence: 99%